Cognitive Control and Bilingualism: The Bilingual Advantage Through the Lens of Dimensional Overlap - Bellegarda, Melodie; Macizo, Pedro (Frontiers in Psychology, 2021)
Past research shows that the bilingual experience may enhance cognitive executive function. In this experiment, we evaluated cognitive control in bilinguals relative to monolinguals by using a dimensional overlap model to predict performance in a task composed of Stroop and Simon stimuli. A group of 24 Spanish monolinguals and 24 bilinguals with differing first languages and all having Spanish as a second language (L2) did a picture naming task and a task composed of Stroop and Simon stimuli, where the effect of different overlap conditions (spatial/color) between stimuli and responses were examined. The tasks were performed in Spanish for both groups and performance was measured with behavioral and electrophysiological measures. We hypothesized that the bilinguals’ daily language practice in L2 reflected overlap conditions similar to the Simon task. Both naming a picture in L2 and the Simon task would involve conflict at the response level. L2 picture naming entails interference between two potential oral responses, to name in L2 vs. L1 (correct vs. incorrect responses, respectively). Similarly, incongruent stimuli in the Simon task produce interference because the irrelevant dimension (spatial location) overlap with an incorrect response. In contrast, the Stroop task involves a different type of conflict between two overlapping stimulus dimensions (the ink color and the color meaning).We predicted for these reasons a superior performance in Simon tasks over Stroop tasks for bilinguals, while monolinguals were expected to have a similar performance in both tasks. We also expected to see a correlation between the performance on the picture naming task and the Simon task in bilinguals. However, the behavioral results did not confirm this hypothesis. In fact, both groups had similar congruency effects as measured by reaction times and error rates, and there was no correlation between the picture naming and Simon task in bilinguals. Despite this, the electrophysiological data suggested a relationship between the picture naming task and the P300 congruency effect in bilinguals. Our findings provide insights into the neurocognitive bases of language and serve as a research avenue for language behaviors in bilinguals.